The losers [videorecording (DVD)] - Berg, Peter, 1964-; Vanderbilt, James; Morgan, Jeffrey Dean, 1966-; Saldana, Zoë, 1978-; Evans, Chris, 1981-; Elba, Idris; Short, Columbus, 1982-; Jaenada, Óscar, 1975-; McCallany, Holt; Macdissi, Peter; Patric, Jason; Diggle, Andy (Warner Home Video, 2010)
An explosive tale of double-cross and revenge centers upon the members of an elite U.S. Special Forces unit sent into the Bolivian jungle on a search and destroy mission. The team; Clay, Jensen, Roque, Pooch and Cougar; find themselves the target of a lethal betrayal instigated from inside by a powerful enemy known only as Max. Presumed dead, the group makes plans to even the score when they're joined by the mysterious Aisha, a beautiful operative with her own agenda.